Sensitivity Analysis of SWAT Model in a Tropical Watershed, East Java - Sujarwo, Mohamad Wawan; Indarto, Indarto; Mandala, Marga (Anuário do Instituto de Geociências, 2023)
Brantas watershed has approximately 14,103 km2 and play an essential role in supplying water for about 30% of the East Java population. Management of water resources in this watershed has become a challenging issue. Conformity of modeling processes and result to mimic the existing hydrological processes is still in question. This study aims to analyze the sensitive parameters of the Soil & Water Assessment Tool (SWAT) model on the watershed. Hydrological processes are observed both monthly and annually. Sensitivity analysis using the SWAT-CUP tool show 18 sensitive parameters. 9 parameters have more than a 50% sensitivity level. 4 are correlated to the soil layer’s runoff generation and water movement. Then, 8 parameters correlated to baseflow calculation. Simulation results illustrate the strong effect of climate change (especially rainfall) on water yield and sedimentation.